Pentingnya Soft Skill dan Pengalaman Kerja dalam Meningkatkan Kinerja Karyawan Penjual Kosmetik - Resha Afrilla; Faizal Mulia; Asep Muhamad Ramdan (Politeknik Negeri Bengkalis, 2020)
The purpose of this study is to measure the effect of soft skills and work experience on the performance of cosmetics sales employees. The variables in this study are soft skills (X1) and work experience (X2), and employee performance (Y). This research uses a quantitative method with an associative approach, by distributing questionnaires to 30 respondents. The data analysis technique used is multiple linear regression seen from the R Square value of 0.880 which means that the influence of soft skills and work experience on the performance of cosmetics sales employees is 88% and the remaining 12% is influenced by other factors not present in this study. From the results of the correlation coefficient test, it can be seen that the R value shows a result of 0.938, which means there is a very strong relationship between soft skills and work experience on the performance of cosmetics sales employees. Soft skill variables affect the performance of cosmetics sales employees, and work experience variables affect the performance of cosmetics sales employees, and the two variables namely soft skills and work experience simultaneously affect the performance of cosmetics sales employees.